DEVELOPMENT OF PREDICTIVE MODELS OF LAND USE CHANGE IN VIETNAM - Vasily F. Kovyazin; Thi Xuan Nguyen (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance. Vietnam is an agricultural country, but at present its development is following the path of industrialization, and the government remained concerned about the quantity and quality of agricultural land. Therefore, assessing the resource potential of different land uses and forecasting land-use trends in Vietnam play a key role in the country's land management. The resource potential of lands was studied for the administrative area of Tienhai district, which is a coastal region of the country, where the agricultural sector of the economy prevails and many types of land use are typical. The main aim of the research is to assess land suitability for different types of land use for predicting the trend of their use in the future. Object of the researches is the state land of Tienhai district in the Socialist Republic of Vietnam. Methods: methods of empirical level: description, observation, measurement, comparison, questioning, generalization and modeling. To identify the dynamics of land plots of different categories the authors have used the method of satellite images, and for their processing – GIS-technology. FAO (food and agriculture organization of the United Nations) and peer review methods were applied to assess land suitability for different land uses. The value of land transformation coefficients for different types of land use is calculated by the method of analytical hierarchical Saaty procedure. Markov chains and modern computer programs and technologies were used to develop a predictive model of land use transformation in Vietnam. Results. Based on the interpretation of satellite images of the territory and GIS technologies the authors plotted the matrix of land transformation probability in Tienhai from 2005 to 2015. The normalized vector of relative importance of the transformation factors when assessing resource potentials of the territory for different types of land use according to the method of analytical hierarchy Saaty procedure was formed with the help of experts. The authors designed the schematic maps of land suitability for different types of land and predicted the areas of land use within the studied region in 10 years.